2014
DOI: 10.1556/avet.2014.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adiponectin receptors 1 and 2 in the ovary and concentration of plasma adiponectin during the oestrous cycle of the pig

Abstract: The aim of this study was to compare the expression levels of adiponectin receptor 1 and adiponectin receptor 2 mRNAs and proteins in porcine ovaries during four stages (days 2 to 3, 10 to 12, 14 to 16, 17 to 19) of the oestrous cycle and to measure adiponectin plasma concentrations during the same phases of the cycle. Higher mRNA expression of adiponectin receptor 1 was detected in porcine granulosa cells than in corpora lutea and theca cells (P < 0.01). In contrast, higher gene expression of adiponectin rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Our earlier studies indicated that the AdipoR protein expression varied both during different phases of the estrous cycle as well as between AP and NP (19). Namely, the AripoR1 protein content was elevated in AP during the luteal phase, which seems to correlate with the plasma adiponectin levels reported by Maleszka et al (29). Interestingly, AdipoR2 protein was elevated on days 10 -12 in AP and on days 10 -12 and 17-19 in NP (19).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Our earlier studies indicated that the AdipoR protein expression varied both during different phases of the estrous cycle as well as between AP and NP (19). Namely, the AripoR1 protein content was elevated in AP during the luteal phase, which seems to correlate with the plasma adiponectin levels reported by Maleszka et al (29). Interestingly, AdipoR2 protein was elevated on days 10 -12 in AP and on days 10 -12 and 17-19 in NP (19).…”
Section: Discussionmentioning
confidence: 53%
“…A study by Takemura et al (45) suggested that the increasing concentrations of estradiol in the human endometrium during the late proliferative phase (late follicular phase) may cause a decrease in adiponectin expression. Furthermore, Maleszka et al (28,29) indicated that both the level of adiponectin in the porcine plasma and adiponectin expression in the porcine ovary are lower during the follicular phase than in the luteal phase, which clearly indicates the influence of sex steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultures for each individual were performed in duplicate. The dose of adiponectin was equivalent to physiological concentration (Maleszka et al 2014b). The alamarBlue test (MP Biomedicals, USA) revealed that the treatment did not affect the viability of the cultured cells.…”
Section: In Vitro Cultures Of the Luteal Cellsmentioning
confidence: 99%